2017
DOI: 10.14744/anatoljcardiol.2016.7461
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of intravascular ultrasound-guided drug-eluting stent implantation among patients with complex coronary lesions: a comprehensive meta-analysis of 15 clinical trials and 8,084 patients

Abstract: Objective:The effects of intravascular ultrasound (IVUS)-guided drug-eluting stent (DES) implantation in patients with complex coronary artery lesions remains to be controversial. This study sought to evaluate the outcomes of IVUS guidance in these patients.Methods:The EMBASE, Medline, and other internet sources were searched for relevant articles. The primary endpoint was major adverse cardiac events (MACE), including all-cause mortality, myocardial infarction (MI), and target-vessel revascularization (TVR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…This updated meta-analysis extended the superior results from our prior citation (11), among which a new RCT (16) focusing on exploring the efficacy of the IVUS guidance in patients suffering from unpro- (16). In fact, the large ULTIMATE trial (6) (intravascular ultrasound-guided versus angiography-guided implantation of drug-eluting stent in all-comers) has indicated that DES implantation under IVUS guidance could significantly reduce the TVF by analyzing the largest sample size (IVUS guidance vs. angiography guidance, 724 vs. 724, respectively), which will make the dominant position of IVUS guidance in all-comer patients well established.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This updated meta-analysis extended the superior results from our prior citation (11), among which a new RCT (16) focusing on exploring the efficacy of the IVUS guidance in patients suffering from unpro- (16). In fact, the large ULTIMATE trial (6) (intravascular ultrasound-guided versus angiography-guided implantation of drug-eluting stent in all-comers) has indicated that DES implantation under IVUS guidance could significantly reduce the TVF by analyzing the largest sample size (IVUS guidance vs. angiography guidance, 724 vs. 724, respectively), which will make the dominant position of IVUS guidance in all-comer patients well established.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, the ULTIMATE trial (6) (intravascular ultrasound-guided versus angiography-guided implantation of drug-eluting stent in all-comers) demonstrated that DES implantation under IVUS guidance could significantly reduce the target vessel failure (TVF) in all-comers, compared to angiography guidance. In fact, several large registries (7,8) and randomized controlled trials (RCT) (9,10), as well as several meta-analyzes (11,12), also indicated the benefits of IVUS-guided DES implantation in patients with complex coronary lesions, which were mainly in terms of the reduced risk of major adverse Inclusion and exclusion criteria All eligible citations should meet the following criteria: (1) enrolled adult patients (age from 18 to 90 years) with complex coronary lesions as defined above; (2) randomized clinical trials comparing IVUS versus CAG-guided DES implantation and performing ≥1-year follow-up; and (3) reported relevant results of adverse clinical events. The exclusion criteria were as follows: (1) nonrandomized or non-English trials; (2) BMS implantation only or patients implanted with both BMS and DES, while the relevant data of DES were not provided; (3) duplicated studies, or different studies using the same sample origin.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year a meta-analysis of 10 studies was performed by Ye et al indicating that IVUS guidance of LMCA stenting reduced the risk of all-cause mortality by 40% and cardiac death by 53% compared with conventional angiography-guided procedures, these data were supported by a complex lesion meta-analysis performed by Fan et al these results are not matching our study as regards mortality benefit with IVUS guidance [10].…”
Section: Angiographic Guided Group (N=64 Patients)contrasting
confidence: 66%
“…However, it still remains unclear if IVUS guidance in DES implantation would have positive effects in patients with ULMCA stenosis. Two recent meta-analyses (9, 10) had indicated the benefits of IVUS-guided DES implantation but in which the mainly analyzed population were these patients with composite of complex coronary lesions. Several previous observational clinical trials indicated similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent observational clinical trials (3, 7) and one randomized trial (8) with a small sample size had reported the positive effects of IVUS-guided DES implantation for patients with ULMCA stenosis, mainly appearing in decreased risk of mortality. In fact, several meta-analyses published recently had also confirmed the benefits of IVUS guidance in DES implantation, though the mainly analyzed population were patients with complex coronary lesions (9, 10). However, these over-mentioned data were mostly from observational trials or small randomized trial, and it still remains unclear to evaluate the benefits of IVUS guidance in DES implantation for a left main lesion.…”
Section: Introductionmentioning
confidence: 99%